Методи шахрайства у мережі Інтернет - Сабадаш, Іванна; Думанський, Нестор (Видавництво Львівської політехніки, 2020)
The activity of scammers was analyzed: methods and means of attracting users to visit illegal websites and provide their personal, compromising or financial information.
Keywords: шахрайство; веб-сайт; інформатизація; фішинг